Hubungan Kebersyukuran dengan Body Image pada Emerging Adulthood Pengguna Tiktok - Haniyah Salsabila; Halimah, Lilim (Bandung Conference Series: Psychology Science, 2024)
Abstract. Thoughts about skinny and ideal body on social media TikTok raise the impact of body image negative and social comparison on most emerging adulthood users. There are various factors that cause the individual to feel dissatisfied with their body image, including a low degree of gratitude that leads to a negative body image. The aim of this study is to investigate the relationship between gratitude and body image in the emerging adulthood of TikTok users in Bandung. The method used is quantitative correlation. The sample consisted of 371 emerging adulthood TikTok users in Bandung City who were selected using accidental sampling techniques. Measures used are The Islamic Gratitude Scale (IGS-10) constructed by Rusdi A et al. (2021) to measure gratitude and the Multidimensional Body Self Relations Questionnaire-Appereance Scales (MBSRQ-AS) of Cash (2000) which have been adapted by Khairani and al. (2019) for measuring body image. Data analysis was done using Spearman's correlation test. The research results indicate a significant relationship between gratitude and body image (r = 0.363, p = 0.001), although the correlation is low. This means that the higher the gratitude of emerging adults who use TikTok in Bandung, the more positive their body image. This study concludes that gratitude plays an important role in improving body image in emerging adulthood TikTok users in Bandung City so it is important to develop awareness and practice gratitude to help individuals deal with body image problems. Abstrak. Penggambaran mengenai tubuh ramping dan ideal di media sosial TikTok menimbulkan dampak ketidakpuasan tubuh dan perbandingan sosial pada sebagian besar pengguna emerging adulthood. Berbagai faktor yang melatarbelakangi individu merasa tidak puas dengan bentuk tubuhnya, diantaranya karena rendahnya rasa syukur yang selanjutnya menimbulkan body image negatif. Tujuan penelitian ini adalah untuk meneliti hubungan antara kebersyukuran dengan body image pada emerging adulthood pengguna TikTok di Kota Bandung. Metode yang digunakan adalah kuantitatif korelasional. Sampel penelitian terdiri dari 371 emerging adulthood pengguna TikTok di Kota Bandung yang dipilih menggunakan teknik accidental sampling. Alat ukur yang digunakan adalah The Islamic Gratitude Scale (IGS-10) yang dikonstruksikan oleh Rusdi A et al. (2021) untuk mengukur kebersyukuran dan Multidimesional Body Self Relations Questionnaire-Appereance Scales (MBSRQ-AS) dari Cash (2000) yang telah diadaptasi oleh Khairani et al. (2019) untuk mengukur body image. Analisis data dilakukan menggunakan uji korelasi Spearman’s. Hasil penelitian menunjukkan terdapat hubungan signifikan antara rasa syukur dan body image (r = 0.363, p = 0.001<0.05), meskipun hubungan tersebut rendah. Artinya, semakin tinggi rasa syukur emerging adulthood pengguna TikTok di Kota Bandung, maka semakin positif body image mereka. Penelitian ini menyimpulkan bahwa rasa syukur berperan penting dalam memperbaiki body image pada emerging adulthood pengguna TikTok di Kota Bandung sehingga penting untuk mengembangkan kesadaran dan praktik rasa syukur agar dapat membantu individu mengatasi masalah body image.